2012
DOI: 10.1111/j.1365-3156.2012.02976.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in health worker performance after implementing the Integrated Management of Childhood Illness strategy in Benin

Abstract: Abstractobjective Training health workers to use Integrated Management of Childhood Illness (IMCI) guidelines can improve care for ill children in outpatient settings in developing countries. However, even after IMCI training, important performance gaps exist. One potential reason is that the effect of training can rapidly wane. Our aim was to determine if the performance of IMCI-trained health workers deteriorated over 3 years.methods We studied two departments in Benin. First, we performed a record review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…Few studies were found that specifically tested these approaches in the primary care setting in LMICs, but they have been used effectively in Myanmar (Aung et al 2012). In Benin, direct case observation of IMCI was associated with higher HCW performance than a simulated client method which the authors attributed to the Hawthorne Effect (Rowe et al 2012). This effect was similar to other studies comparing conspicuous observation to patient interviews and to patient registers (Rowe et al 2006)…”
Section: Resultsmentioning
confidence: 99%
“…Few studies were found that specifically tested these approaches in the primary care setting in LMICs, but they have been used effectively in Myanmar (Aung et al 2012). In Benin, direct case observation of IMCI was associated with higher HCW performance than a simulated client method which the authors attributed to the Hawthorne Effect (Rowe et al 2012). This effect was similar to other studies comparing conspicuous observation to patient interviews and to patient registers (Rowe et al 2006)…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that active on-going efforts to support changes in practice may be required beyond the initial implementation period (e.g. [45, 48, 49]. This has important resource implications for health planners looking to embed improvements into routine clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three scientific publications reporting interventions to improve child health in Nigeria, two 37,39 evaluated intervention programmes already operational while one 38 implemented an intervention to generate policy relevant evidence (Table 3). The existing interventions evaluated included health worker performance after implementing the integrated management of childhood illness strategy and treatment regimens for acute diarrhea in children.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 76 publications yielded in category 2, 7(9.2%) 30-36 satisfied the study inclusion criteria regarding newborn health and were selected (Table 2), while of the 249 publication from category 3, only 3 (1.2%) 37-39 met the study inclusion criteria regarding child health and were selected (Table 3). The flowchart of the study selection procedure is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%